2001
DOI: 10.1038/labinvest.3780312
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Caspase-1/Interleukin-1β–Converting Enzyme on Acinar Cell Necrosis and Apoptosis in Severe Acute Experimental Pancreatitis

Abstract: SUMMARY:There is recent experimental evidence that inhibition of caspase-1/interleukin-1␤ converting enzyme (ICE) significantly ameliorates overall severity and survival in severe acute experimental pancreatitis. However, little is known about the effects of this approach on the dynamics and mechanisms of local acinar cell damage, which we aimed to investigate in the present study. Severe acute pancreatitis (SAP) was induced by retrograde infusion of 4% sodium taurocholate in rats treated with isotonic sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 38 publications
3
32
0
1
Order By: Relevance
“…Macrophage inflammatory protein 1 alpha, a protein involved in chemotraction of macrophages, was induced in animals with morphologic pancreatic lesions, while expression was low or not detectable in the pancreata of animals treated with two cigarettes twice a day not showing altered histology [23]. Similar expression profiles were detected for interleukin 1 beta, a molecule expressed by acinar cells and immune cells which is involved in the first line of immune response [24] and transforming growth fact beta 1 indicating the involvement of TGF beta in reorganization of the pancreatic acinar tissue [25]. These data indicated that the inhalation of cigarette smoke induces an ongoing pancreatic inflammatory process related to transforming growth fact beta leading to acinar cell destruction with reorganization of circumscribed areas of the exocrine pancreas to connective tissue.…”
Section: Cigarette Smoke-induced Pancreatic Inflammationmentioning
confidence: 52%
“…Macrophage inflammatory protein 1 alpha, a protein involved in chemotraction of macrophages, was induced in animals with morphologic pancreatic lesions, while expression was low or not detectable in the pancreata of animals treated with two cigarettes twice a day not showing altered histology [23]. Similar expression profiles were detected for interleukin 1 beta, a molecule expressed by acinar cells and immune cells which is involved in the first line of immune response [24] and transforming growth fact beta 1 indicating the involvement of TGF beta in reorganization of the pancreatic acinar tissue [25]. These data indicated that the inhalation of cigarette smoke induces an ongoing pancreatic inflammatory process related to transforming growth fact beta leading to acinar cell destruction with reorganization of circumscribed areas of the exocrine pancreas to connective tissue.…”
Section: Cigarette Smoke-induced Pancreatic Inflammationmentioning
confidence: 52%
“…In other models of in vivo inflammation, the role of ICE has been characterized in more detail. For instance, beneficial effects of ICE blockade or ICE deficiency have been demonstrated in toxin-induced pancreatitis (32,33) and collagen-induced arthritis (34).…”
Section: Discussionmentioning
confidence: 99%
“…Some experiments have proved that the contents of IL-1β are positively correlated with the mortality rates of rats [18]. Paszkowski et al [19,20] have found that IL-1β mRNA is expressed in normal lung tissues. In SAP, the expression of IL-1β mRNA is significantly enhanced, and the expression levels of IL-1β mRNA are parallel to the severity of SAP.…”
Section: Discussionmentioning
confidence: 99%